Determinants of red blood cell transfusion in pediatric trauma patients admitted to the intensive care unit. Issue 1 (2nd October 2016) - Roumeliotis, Nadia; Ducruet, Thierry; Bateman, Scot T.; Randolph, Adrienne G.; Lacroix, Jacques; Emeriaud, Guillaume; ,
Abstract : BACKGROUND: There are no well‐designed prospective studies evaluating transfusion practices in pediatric trauma. We sought to describe red blood cell (RBC) transfusion practices in trauma patients who were admitted to a pediatric intensive care unit (PICU). STUDY DESIGN AND METHODS: This study is a post‐hoc analysis of a prospective, 6‐month observational study in 30 PICUs. We studied a total of 580 patients aged less than 18 years who had been admitted to a PICU for more than 48 hours, including 95 who were trauma patients. RESULTS: Trauma patients more frequently received transfusion before PICU admission (p < 0.001), were older (p < 0.0001), and more frequently were mechanically ventilated (p = 0.05). In the PICU, trauma patients received more transfusions (55% vs. 37%; p < 0.001), although admission hemoglobin levels were similar in both groups (p = 0.86). The mean (± standard deviation) pretransfusion hemoglobin level in the PICU was 9.0 ± 2.4 g/dL for trauma patients compared with 8.3 ± 2.4 g/dL for nontrauma patients (p = 0.09). Among the trauma patients, transfusion was associated with younger age, higher Pediatric Logistic Organ Regression scores, mechanical ventilation, bleeding, and transfusion before PICU admission. Multivariate regression demonstrated that receiving an RBC transfusion before admission was strongly associated with receiving a blood transfusion in the PICU (p = 0.008). CONCLUSION: Trauma patients are at high risk for receiving an RBC transfusion both before and during their PICU stay, despite a similar transfusion threshold compared with nontrauma patients. Transfusion before PICU admission is a strong determinant, suggesting ongoing bleeding that will require re‐transfusion. Further studies are needed to evaluate whether a restrictive transfusion strategy can safely be considered in these patients.